Migration from China to the EU: the challenge within Europe - Wu, Bin; Latham, Kevin (Palgrave Macmillan, 2014)
At the beginning of the 21st Century, we have witnessed a rapid growth in Chinese immigration to the European Union (EU), which has had a profound impact on local Chinese communities in various ways. This chapter aims to reveal the latest developments in Chinese immigration in the EU, as well as the new dynamics, features and impacts on local Chinese communities. The above questions are addressed by a combination of secondary data analysis and our own observation in Italy and the UK in recent years. Some challenging issues facing Chinese communities are highlighted.